Very low birth weight is associated with reduced right ventricular function detected by strain imaging in early adulthood – findings from a prospective matched cohort study. (25th November 2020) - Greer, C; Adamson, P; Harris, S; Horwood, J; Troughton, R; Darlow, B
Abstract: Introduction: Being born at very low birth weight (VLBW, <1500g) is associated with increased rates of cardiopulmonary disorders in childhood. As survivors age, late cardiac effects, including right ventricular (RV) remodelling and occult pulmonary hypertension are emerging. Strain imaging provides prognostically important information regarding RV dysfunction in diverse cardiopulmonary conditions however, these indices have not previously been described within VLBW cohorts. Purpose: To assess differences in right heart function using strain in young adults born at VLBW, compared to normal weight term born controls. Methods: The New Zealand Very Low Birth Weight Study has followed all infants born in 1986 with birth weight <1500g. Of 323 survivors to adulthood, 228 (71%) had echocardiograms at 26–30 years which were compared to age and sex-matched term-born, normal-weight controls (n=100). RV global longitudinal strain (GLS) was measured by speckle tracking echocardiography by an investigator blinded to group allocation. Established measures of RV function (fractional area change (FAC), tricuspid annular systolic velocity (RV S') and tricuspid regurgitation velocities) were also obtained. Results: VLBW subjects were smaller than their peers as young adults (Table 1). Strain measurement showed reduced myocardial deformation among VLBW subjects (RV myocardial GLS: −22.4% vs −23.5%, p=0.008; RV endocardial GLS: −23.6% vs −24.9%, p=0.005; free wall myocardial GLS −25.2% vs −26.1%, p=0.039; free wall endocardial GLS −26.7% vs −27.9%, p=0.009). TR velocity was higher in VLBW: 224 cm/s v 210 cm/s (p=0.002). RV S', and FAC were not different. Conclusion: Young adults born at VLBW have impaired myocardial strain despite preserved RV function as assessed by standard techniques. Echocardiographic strain imaging may be an important tool to detect subclinical RV dysfunction. Funding Acknowledgement: Type of funding source: None